KEMAMPUAN BERPIKIR KREATIF SISWA DALAM MEMECAHKAN MASALAH IPAS MELALUI MODEL PEMBELAJARAN PROBLEM BASED LEARNING DENGAN MEDIA BERBASIS VIDEO ANIMASI - Sari , Ratna Kumala; Dian Septi Nur Afifah; Moh. Gufron (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Creative thinking skills, as one of the 21st-century competencies, need to be developed from an early age, especially in the learning of Science and Social Studies (IPAS). However, IPAS instruction in elementary schools still tends to be conventional, teacher-centered, and lacks the use of instructional media, thereby limiting active student engagement in problem-solving activities. This study aims to describe the implementation of the Problem-Based Learning (PBL) model supported by animated video media, as well as to describe students’ creative thinking abilities in solving IPAS-related problems. The study employed a descriptive qualitative approach with subjects consisting of one teacher and six fifth-grade students from SD Negeri 1 Batokan, selected based on their Creative Thinking Ability Level (Tingkat Kemampuan Berpikir Kreatif/TKBK). Data collection techniques included observation, problem-solving tests, and in-depth interviews based on four indicators of creative thinking: fluency, flexibility, originality, and elaboration. The results showed that the implementation of PBL with animated video media facilitated interactive and contextual learning and promoted varied development of students' creative thinking abilities. Students in the very creative category (TKBK 4) fulfilled all creative thinking indicators, while those in the creative (TKBK 3) and moderately creative (TKBK 2) categories excelled in only some of the indicators. The implications of this study indicate that integrating the PBL model with visual media such as animated videos can serve as a relevant and applicable alternative to foster students' creativity and improve the quality of IPAS learning in elementary schools.